Worldwide patterns and trends in ovarian cancer incidence by histological subtype: a population-based analysis from 1988 to 2017Research in context - Yi-Fan Wei; Li Ning; Yi-Lin Xu; Jing Ma; Dong-Run Li; Zan-Fei Feng; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Peng Li; Yong-Pei Yu; Dong-Hui Huang; et al. (EClinicalMedicine)
Summary: Background: Ovarian cancer (OC) is a heterogeneous malignancy with multiple histological subtypes, showing global variability in incidence. Temporal changes in diagnostic criteria and risk factors might influence the incidence and distribution of OC and its subtypes. Methods: This study analyzed incidence patterns (2013–2017) and trends (1988–1992 to 2013–2017) of OC and its subtypes across 65 and 40 countries, respectively. Data were extracted from the Cancer Incidence in Five Continents (CI5 Ⅻ) and CI5plus databases (accessed in June 2024). Annual percent changes were computed to describe trends in age-standardized rates (ASRs) of OC and its subtypes. Proportions of ASR for each subtype relative to the ASR of OC for individual countries were calculated. Findings: The incidence of OC displayed marked disparities across regions and Human Development Index (HDI), with the highest ASRs in Eastern and Central Europe and very high HDI regions, and the lowest in Africa, Asia, and medium HDI regions. Despite stable trend in ASRs of OC globally, notable declines were observed in Europe, America, and Oceania, in contrast to increases in Asian countries like Japan and South Korea. Globally, serous carcinomas remained the most prevalent subtype. European countries exhibited a higher proportion of serous carcinomas, while Asian countries had a higher proportion of endometrioid and clear cell carcinomas. Although trends in subtypes also remained stable, ASRs increased over time for serous carcinomas and germ cell tumor in most countries, while mucinous carcinomas and adenocarcinoma NOS showed a decline. Interpretation: Variations in global patterns and trends in OC incidence and its subtypes might be influenced by genetic and reproductive factors. Consequently, region-specific prevention strategies and ongoing surveillance are essential to mitigate the burden of OC. Funding: The National Key Research and Development Program of China (No.2022YFC2704205), the Natural Science Foundation of China (No.82073647, 82373674, and 82103914), Outstanding Scientific Fund of Shengjing Hospital, 345 Talent Project of Shengjing Hospital of China Medical University, the Max Planck – University of Helsinki Center from the Jane and Aatos Erkko Foundation (No.210046), the Max Planck Society (No.5714240218), the University of Helsinki (No.77204227), and the European Union (ERC Synergy, BIOSFER, 101071773).